Effect of Chitosan on Ethyl Cellulose and Eudragit RS 100 Microspheres - Agnimitra, D.; Ipsita, B.; Sumit, M.; Moonmun, D.; Durga, M.; Si, S.; Barik, B.B. (Asian Journal of Chemistry, 2010)
The aim and objective of the present investigation is to study the effect of chitosan on the various characteristics of Eudragit RS 100 and ethyl cellulose microspheres which were formulated by o/o emulsion, solvent evaporation method using methanol, acetone, light liquid paraffin system. Effect of chitosan was evaluated on several aspects such as particle size, drug content and entrapment, morphology, drug-polymer interaction and in vitro release study. It was found that chitosan had great influence on the various properties of ethyl cellulose and Eudragit RS 100 microspheres containing lamivudine sulphate as drug candidate.